2009
DOI: 10.1111/j.1468-5973.2009.00555.x
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance in the Context of Crises: Towards a Stakeholder Theory of Crisis Management

Abstract: In this paper, we take a step towards developing a stakeholder theory of crisis management. We argue that, in the context of crises, adopting the principles of a stakeholder model of corporate governance will lead companies to engage more frequently in proactive and/or accommodating crisis management behaviour even if these crisis management behaviours are not perceived to maximize shareholder value. We also propose a mechanism that may explain why the stakeholder model may be associated with more successful c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
114
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 92 publications
0
114
0
5
Order By: Relevance
“…Initial analysis indicated that government units are more interested in building BCMS than private companies are, which probably results from the scale of economic activity and public utility of that services [Alpaslan, Green, and Mitroff 2009]. At the same time, an assumption emerged that awareness of business continuity management in a systematic way arises along with the period a business is run on the market.…”
Section: Hypothesesmentioning
confidence: 99%
“…Initial analysis indicated that government units are more interested in building BCMS than private companies are, which probably results from the scale of economic activity and public utility of that services [Alpaslan, Green, and Mitroff 2009]. At the same time, an assumption emerged that awareness of business continuity management in a systematic way arises along with the period a business is run on the market.…”
Section: Hypothesesmentioning
confidence: 99%
“…Alpaslan, Green and Mitroff (2009) add that understanding stakeholder theory and adopting a stakeholder model is useful as a corporate governance tool that can be applied and used in crisis situations.…”
Section: Stakeholder Identification and Engagementmentioning
confidence: 99%
“…The consequences of a crisis also depend on how the organization is able to manage the crisis, which crisis management strategy it chooses and how it ___________________________________________________________________________ 2018 / 32 8 communicates with the stakeholders (Dowling, 2002;Coombs, 2007;Alpaslan, Green & Mitroff, 2009;Lerbinger, 2012). Quite frequently, communication is the factor determining the success of crisis management, as well as the financial and reputation damage.…”
Section: Business Organization Crises Their Concept and Principal Asmentioning
confidence: 99%